2013
DOI: 10.3349/ymj.2013.54.4.912
|View full text |Cite
|
Sign up to set email alerts
|

Pure Laparoscopic Radical Cystectomy with Ileal Conduit: A Single Surgeon's Mid-Term Outcomes

Abstract: PurposeThe use of laparoscopic radical cystectomy (LRC) for muscle-invasive bladder cancer is not yet widespread because of the technical difficulties of the procedure and the lengthy operating time. In this study, we report a single surgeon's experience with LRC.Materials and MethodsThirty patients (25 men and 5 women) with bladder cancer underwent LRC and ileal conduit by a single surgeon between November 2007 and May 2011. An extracorporeal urinary diversion was performed through 5-6 cm midline incision for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In our series, the mean operative time, hospitalization days, average blood loss, and blood transfusion rate were 577.0±126.4 min, 29.4±9.2 days, 280.0±130.38 ml, and 40%, respectively, results were similar with the study of Park et al ( 12 ). However, the operative time was longer than those in other series.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our series, the mean operative time, hospitalization days, average blood loss, and blood transfusion rate were 577.0±126.4 min, 29.4±9.2 days, 280.0±130.38 ml, and 40%, respectively, results were similar with the study of Park et al ( 12 ). However, the operative time was longer than those in other series.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that laparoscopic radical cystoprostatectomy with intracorporeal ileal was conducted for urinary diversion for the first time in 2000 ( 10 ). Since then, several groups reported the use of laparoscopy for radical cystectomy and indicated the safety and practicability of LRC ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contemporary studies have shown that open radical cystectomy morbidity is higher than 50% in reference centers. Most significant complications, such as infections, paralytic ileus, operative wound dehiscence and urinary or intestinal fistulas can be life-threatening in about 10 to 20% of cases ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radical cystectomy is indicated for persistent Tis, T1 and Ta high-grade disease when BCG therapy is ineffective, as well as for muscle-invasive cancers. Minimally invasive radical cystectomy using laparoscopy or the robotic platform is performed at selected institutions (30,31).…”
Section: Local and Locoregional Bladder Cancermentioning
confidence: 99%